Properties of geopolymer pervious concrete made with GGBS - Babu Chokkalingam, Ramesh; Subbu L, Prakkash; Raj R, Thangavel; Sawant M, Shubham; ., . (International Journal of Engineering and Technology, 2018)
Pervious concrete is a light weight concrete containing voids in the range of 14 to 31%. The usage of pervious concretes has been in- creased due to its merits on pollution control and environmental considerations. The pervious concretes are also used to reduce the storm water runoff and recharges the underground water table. Eventhough the pervious concrete has lot of merits, it also has consider- able demerits related to strength issues. In order to achieve the strength high cement content mixes may be incorporated which is not a viable solution. In this paper, geopolymer technology has been used to develop pervious concrete. Geopolymer pervious concrete is pro- duced using GGBS as raw material and sodium hydroxide and sodium silicate as activator solution. Five mixes have been developed with varying GGBS content of 450, 460, 470, 480 and 490 kg/m3. The cement to aggregate ratio is fixed at 1:3 for all the mixtures and the water cement ratio is kept constant at 0.3. The compressive strength revealed that strength of around 20 MPa was attained for all the mixtures and strength increases with respect to the increase in GGBS content. There was not significant changes in the permeability property since the aggregate cement ratio is maintained for all the mixtures.Â Â